Countercyclical risk aversion: beyond financial professionals - König-Kersting, Christian; Trautmann, Stefan T. (Journal of behavioral and experimental finance, 2018)
We test if Cohn et al.’s (2015) experimental results on countercyclical risk aversion exhibited by financial professionals generalize to a standard student sample. In our sample, we do not find an effect of stock market bust or boom on subjects’ investments. We do not find a systematic emotional reaction, nor do we find an effect of variation in the emotional state (especially fear) on investment. Our results add to the literature documenting behavioral differences between financial professionals and non-professionals and, taking a policy perspective, underline the need for careful external validity checks of single sample experiments.